Aldosterone Target NGAL (Neutrophil Gelatinase–Associated Lipocalin) Is Involved in Cardiac Remodeling After Myocardial Infarction Through NFκB Pathway. Issue 6 (December 2017) - Martínez-Martínez, Ernesto; Buonafine, Mathieu; Boukhalfa, Ines; Ibarrola, Jaime; Fernández-Celis, Amaya; Kolkhof, Peter; Rossignol, Patrick; Girerd, Nicolas; Mulder, Paul; López-Andrés, Natalia; Ouvrard-Pascaud, Antoine; Jaisser, Frédéric
Abstract : Myocardial infarction (MI) is accompanied by cardiac fibrosis, which contributes to cardiac dysfunction. Mineralocorticoid receptor (MR) antagonists have beneficial effects in patients with left ventricular (LV) dysfunction after MI. We herein investigated the role of the MR target NGAL (neutrophil gelatinase–associated lipocalin) in post-MI cardiac damages. Both higher baseline NGAL and a greater increase in serum NGAL levels during follow-up were significantly associated with lower 6-month LV ejection fraction recovery in a cohort of 119 post-MI patients, as assessed by cardiac magnetic resonance imaging. NGAL protein levels increased in the LV at 7 days post-MI in wild-type mice with MI. This effect was prevented by treatment with the nonsteroidal MR antagonist finerenone (1 mg/kg per day). NGAL knockout mice with MI had lower LV interstitial fibrosis and inflammation, better LV contractility and compliance, and greater stroke volume and cardiac output than wild-type mice with MI at 3 months post-MI. Aldosterone (10 −8 mol/L) increased NGAL expression in cultured human cardiac fibroblasts. Cells treated with aldosterone or NGAL (500 ng/mL) showed increased production of collagen type I. The effects of aldosterone were abolished by finerenone (10 −6 mol/L) or NGAL knockdown. This NGAL-mediated activity relied on NFκB (nuclear factor-κB) activation, confirmed by the use of the NFκB-specific inhibitor BAY11-7082, which prevented the effect of both aldosterone and NGAL on collagen type I production. In conclusion, NGAL, a downstream MR activation target, is a key mediator of post-MI cardiac damage. NGAL may be a potential therapeutic target in cardiovascular pathological situations in which MR is involved. Abstract : Supplemental Digital Content is available in the text.